Design and Development of Cryo-Adsorption Chamber for the Measurement of Methane Uptakes on Activated Carbons and MOFs - Chakraborty, Anutosh (2017)
We have designed and developed the cryo-adsorption chamber to measure methane uptakes on various MOFs and activated carbons for the temperatures ranging from 120 K to 300 K and pressures up to 10 bar with temperature and pressure controls. The experimentally measured data are fitted with the modified Langmuir adsorption (MLA) equation. The MLA isotherm describes all of the isotherm experimental data within the acceptable error ranges. The thermo-physical properties of activated carbon (type Maxsorb III) and MOFs (Fe-BTC) are also presented in this paper. The present isotherm data are compared with other published data and showed the superiority of the present findings in terms of uptake capacity employing the newly designed metal organic frameworks (MOFs).